Marginal Bone Loss around Implants with Internal Hexagonal and Internal Conical Connections: A 12-Month Randomized Pilot Study - Pablo Galindo-Moreno (MDPI AG, 2021)
The aim of this study was to analyze the differences in terms of the marginal bone level (MBL) around implants with either an internal conical or an internal hexagonal implant–prosthesis connection. A randomized clinical trial included patients in need of a single implant-supported restoration. The implant–prosthesis connection was either internal conical or internal hexagonal while maintaining the same type of implant macro- and microarchitecture. Clinical and radiographical variables were registered up to 12 months of follow-up, including MBL. A total of 30 patients were included in the study. The main outcome variable, MBL 12 months after prosthesis delivery, was statistically different in both groups: −0.25 (0.12) vs. −0.70 (0.43) (conical vs. hexagonal; p = 0.033). Differences were also observed at the 3- and 6-month follow-up visits as well as for the MBL change from prosthesis delivery to the 12-month follow-up (−0.15 (0.13) vs. −0.56 (0.44); conical vs. hexagonal; p = 0.023). Correlations between MBL around the implants and radiographic measurements on the adjacent teeth, buccal bone to implant, tissue thickness or keratinized tissue were not significant neither globally nor when analyzed independently by group. In view of such results, it can be concluded that single-unit restorations with internal hexagonal-connection implants induce higher marginal bone loss after 12 months of follow-up from prosthesis delivery than internal conical-connection implants.